Harnessing Mobile Health Technology for Secondary Cardiovascular Disease Prevention in Older Adults: A Scientific Statement From the American Heart Association. Issue 5 (May 2021) - Schorr, Erica N.; Gepner, Adam D.; Dolansky, Mary A.; Forman, Daniel E.; Park, Linda G.; Petersen, Kristina S.; Still, Carolyn H.; Wang, Tracy Y.; Wenger, Nanette K.
Abstract : Secondary prevention of cardiovascular disease (CVD), the leading cause of morbidity and mortality, is critical to improving health outcomes and quality of life in our aging population. As mobile health (mHealth) technology gains universal leverage and popularity, it is becoming more user-friendly for older adults and an adjunct to manage CVD risk and improve overall cardiovascular health. With the rapid advances in mHealth technology and increasing technological engagement of older adults, a comprehensive understanding of the current literature and knowledge of gaps and barriers surrounding the impact of mHealth on secondary CVD prevention is essential. After a systematic review of the literature, 26 studies that used mHealth for secondary CVD prevention focusing on lifestyle behavior change and medication adherence in cohorts with a mean age of ≥60 years were identified. Improvements in health behaviors and medication adherence were observed, particularly when there was a short message service (ie, texting) component involved. Although mobile technologies are becoming more mainstream and are starting to blend more seamlessly with standard health care, there are still distinct barriers that limit implementation particularly in older adults, including affordability, usability, privacy, and security issues. Furthermore, studies on the type of mHealth that is the most effective for older adults with longer study duration are essential as the field continues to grow. As our population ages, identifying and implementing effective, widely accepted, cost-effective, and time-efficient mHealth interventions to improve CVD health in a vulnerable demographic group should be a top health priority. Abstract : Supplemental Digital Content is available in the text.